Spatially resolved Hall effect measurement in a single semiconductor nanowire - Storm, Kristian; Halvardsson, Filip; Heurlin, Magnus; Lindgren, David; Gustafsson, Anders; Wu, Phillip M.; Monemar, Bo; Samuelson, Lars (Nature nanotechnology, 2012)
Efficient light-emitting diodes and photovoltaic energy-harvesting devices are expected to play an important role in the continued efforts towards sustainable global power consumption. Semiconductor nanowires are promising candidates as the active components of both light-emitting diodes 1 , 2 , 3 , 4 , 5 , 6 and photovoltaic cells 7 , 8 , 9 , 10 , primarily due to the added freedom in device design offered by the nanowire geometry. However, for nanowire-based components to move past the proof-of-concept stage and be implemented in production-grade devices, it is necessary to precisely quantify and control fundamental material properties such as doping and carrier mobility. Unfortunately, the nanoscale geometry that makes nanowires interesting for applications also makes them inherently difficult to characterize. Here, we report a method to carry out Hall measurements on single core–shell nanowires. Our technique allows spatially resolved and quantitative determination of the carrier concentration and mobility of the nanowire shell. As Hall measurements have previously been completely unavailable for nanowires, the experimental platform presented here should facilitate the implementation of nanowires in advanced practical devices. Hall effect measurement set-up on a single core–shell semiconductor nanowire enables spatially resolved determination of carrier concentration and mobility in the nanowire shell.